2019
DOI: 10.1002/ese3.499
|View full text |Cite
|
Sign up to set email alerts
|

Performance of a good‐emulsification‐oriented surfactant‐polymer system in emulsifying and recovering heavy oil

Abstract: Considering the significant importance of emulsification for heavy oil recovery, a good‐emulsification‐oriented (GEO) (rather than the conventional ultralow interfacial tension (IFT) oriented) surfactant‐polymer (SP) system was employed to remove heavy oil. Specifically, the emulsification behavior and viscosity‐reduction property of heavy oil in porous media were first studied by flood tests. Then, such a GEO SP was used to displace heavy oil for recovery measurement. It is found that first, as migration incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…The nonionic surfactant has good salt-resistance but poor temperature resistance. Although the anionic-nonamphoteric surfactant has good temperature and salt resistance, it is still presents a challenge for crude oil at high temperatures and high calcium and magnesium content. …”
Section: Introductionmentioning
confidence: 99%
“…The nonionic surfactant has good salt-resistance but poor temperature resistance. Although the anionic-nonamphoteric surfactant has good temperature and salt resistance, it is still presents a challenge for crude oil at high temperatures and high calcium and magnesium content. …”
Section: Introductionmentioning
confidence: 99%
“…Thermal recovery is the most common and successful technology in heavy oil recovery. However, a large amount of heat will be consumed in the process of transferring and heating crude oil, especially for the reservoirs with thin reservoir thickness and bottom water. The cold production of heavy oil has received more and more attention, and surfactant emulsification and viscosity reduction technology is one of the most effective methods due to its good viscosity reduction effect, simple process, and low cost. …”
Section: Introductionmentioning
confidence: 99%
“… 20 evaluated the properties of the emulsions with weak and strong emulsifying agents generated during the surfactant flooding. The viscosity reduction via in situ emulsification was also studied in ref ( 21 ). The authors showed that the O/W emulsion undergoes a decrease in the droplet size while migrating through the porous media.…”
Section: Introductionmentioning
confidence: 99%
“… 27 , 28 An interesting example of silica nanoparticles with a grafted polymer allowed the authors to reversibly stabilize, recover, and break O/W emulsions via pH variation. 29 Surfactant–polymer (see, for instance ref 21 , 30 , 31 ). Surfactant–polymer–nanoparticle systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation